Land use allocation based on interval multi-objective linear programming model: A case study of Pi County in Sichuan Province - Wang, Hongrui; Gao, Yuanyuan; Liu, Qiong; Song, Jinxi (Chinese geographical science, 2010)
Adjusting and optimizing land use structure is one of the essential approaches to solve the conflict between land supply and demand. In this study, an uncertain interval multi-objective linear programming model was established and applied to analyzing the suitability of land use structure in Pi County of Sichuan Province. An adjustment scheme for optimizing land use structure was proposed on the basis of development planning drawn up by the local government. The results are summarized as follows: 1) the optimal adjustment scope for cropland area ranges from 27 976.75 ha to 31 029.08 ha, and the current area is less than the lower limit of the scope; 2) the optimal adjustment scope for garden land area ranges from 4 736.49 ha to 12 967.11 ha, and the current area is less than the lower limit; 3) the optimal adjustment scope for construction land ranges from 7 761.95 ha to 10 393.18 ha, and the current area is greater than the upper limit; 4) the optimal adjustment scope for industry and mining land ranges from 557.29 ha to 693.54 ha, and the current area exceeds the upper limit; and 5) the areas of forest land, grassland and other agricultural land are within the optimal adjustment scope. In order to maximize comprehensive benefit with the limited resources and the demand of sustainable development, the areas of cropland and garden land are supposed to be expanded properly, while the construction land should be controlled and reduced gradually, and the forest land and other agricultural land can be maintained at the current level in short period.